2020
DOI: 10.1332/204674319x15664893823072
|View full text |Cite
|
Sign up to set email alerts
|

Displaying morally responsible motherhood: lone mothers accounting for work during non-standard hours

Abstract: This study examined how lone mothers rationalize their work during non-standard hours (e.g., evenings and weekends), which they perceive as problematic in terms of child wellbeing, and thereby as violating the culturally shared moral order of motherhood. The data comprise interviews with 16 Finnish lone mothers, analysed as accounts, with special focus on their linguistic features. The mothers displayed morally responsible motherhood through: (1) excusing work during non-standard hours as an external demand; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Single mothers drawing primarily on such narratives tended to present work as commensurate with intensive mothering ideals (Hays, 1996) by narrating financial provision as an integral element of this. Such accounts support recent research focused on single mothers suggesting they largely sought to conform to intensive mothering ideals (Moilanen et al ., 2019b). Here, we found that conceptualizing work in this way aligned with part‐time working, organizing work around caregiving and only working as much as was financially necessary for their family.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Single mothers drawing primarily on such narratives tended to present work as commensurate with intensive mothering ideals (Hays, 1996) by narrating financial provision as an integral element of this. Such accounts support recent research focused on single mothers suggesting they largely sought to conform to intensive mothering ideals (Moilanen et al ., 2019b). Here, we found that conceptualizing work in this way aligned with part‐time working, organizing work around caregiving and only working as much as was financially necessary for their family.…”
Section: Discussionmentioning
confidence: 99%
“…Such identity work tended to coincide with downskilling, or no longer seeking progression, yet in all cases continuing to find a way to narrate work as integral to who they are. Further, it was the availability of different work narratives that appeared to influence conformity, or a lack thereof, to intensive mothering ideals, extending previous research (Hays, 1996; Moilanen et al ., 2019b) by considering when and why intensive mothering norms may be challenged in the context of single motherhood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations